The New Brazil : From Backwater to BRIC. - Roett, Riordan (Brookings Institution Press, 2010)
The New Brazil tells the story of that nation's evolution from a remote Portuguese colony into a regional leader, a respected spokesman for the developing world, and an increasingly important partner for the United States and the European Union.